No.253 Lymph Nodes Metastasis in Left-Sided Colorectal Cancer Liver Metastasis (CRLM) Patients: Incidence and Prognosis. (March 2022) - Chang, Jiang; Mao, Yihao; Feng, Qingyang; Chen, Yijiao; Wu, Qi; Zheng, Peng; Zhang, Zhiyuan; Yu, Shanchao; Jiang, Yudong; Wei, Ye; Xu, Jianmin; He, Guodong
Background: No.253 lymph node is the gateway to systemic metastasis for left-sided colorectal cancer. However, the value of D3 resection is still controversial. This study aimed to identify the incidence rate and prognostic value of 253LN metastasis in patients with left-sided colorectal cancer liver metastasis (CRLM) mainly through blood vessels and thus to provide theoretical basis for 253LN resection. Methods: From February 2012 to February 2019, a total of 281 patients who underwent curative resection for both primary and metastatic tumors were collected retrospectively. The clinicopathological and genetic characteristics were compared between 58 patients with positive 253LN and 223 patients with negative. Relapse-free survival (RFS) and overall survival (OS) were compared with Kaplan–Meier method. Cox regression analysis and a forest plot were conducted for RFS. Results: The incidence of 253LN metastasis in left-sided CRLM was 20.64% (58/281). Those with 253LN positive were T4 stage, N2 stage, and D1/D2 lymph nodes metastatic. About 10.3% (8/78) 253LN positive patients were D1/D2 negative. The 253LN metastasis was an independent risk factor for relapse after curative surgery, but not for OS. Patients with 253LN metastasis had worse RFS, especially in female, adenocarcinoma, poorly differentiated, pT3, preoperative serum CA199 < 37 U/mL, bilobar liver metastasis, without preoperative chemotherapy, KRAS, NRAS, or BRAF wild type. Conclusion: The incidence of 253LN metastasis in left-sided CRLM is 20.64%, and skip metastasis rate is 10.3%. The 253LN status is an independent prognostic risk factor for RFS but not for OS after curative surgery. Routine resection of 253LN should be applied in curative surgery of left-sided CRLM.